2020
DOI: 10.3389/fonc.2020.586458
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Prognostic Nomogram for Bladder Cancer With Distant Metastasis: A SEER-Based Study

Abstract: Background: To investigate the impact of marital status on overall survival (OS) and create a prognostic nomogram predicting OS in distant-metastatic bladder cancer (DMBC) patients. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was explored to recruit DMBC patients from 2010 to 2015. Kaplan-Meier survival analysis was used to compare survival differences among different marital status. Univariate and multivariate analyses were used to screen for prognostic factors and then constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…However, CDC is usually insensitive to these types of treatments ( 23 , 25 , 26 ). In previous studies, marital and economic statuses were reported to be associated with prognosis, but these were not defined as risk factors in the present study ( 27 , 28 ). This may be due to the extremely poor prognosis of this disease, with a large number of patients dying in a short time.…”
Section: Discussionmentioning
confidence: 60%
“…However, CDC is usually insensitive to these types of treatments ( 23 , 25 , 26 ). In previous studies, marital and economic statuses were reported to be associated with prognosis, but these were not defined as risk factors in the present study ( 27 , 28 ). This may be due to the extremely poor prognosis of this disease, with a large number of patients dying in a short time.…”
Section: Discussionmentioning
confidence: 60%
“…The nomogram has shown good classification as well as prediction accuracy in both the training set and test set. Further, the AUCs (>0.80) were superior to previous prognostic model (11,27,34) for BLCA patients. The optimized classification accuracy could be partly due to the increased sample size in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…In comparison to SDW and unmarried patients, married patients have better prognosis. The protective effects of married marital status have been reported extensively (26)(27)(28). Most of BLCA cases were male; however, female patients tend to have worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the COBRA model, the Cindex in our nomogram was high both in the training cohort (0.834 vs. 0.712) and validation cohort (0.834 vs. 0.705). Tao et al [26] indicated that marital status was an independent prognostic factor of OS in distant-metastatic BC patients, but its contribution to predicting OS was relative small. They constructed a prognostic models based on SEER population by utilizing eight variables, including marital status, age, tumor grade, histology type, primary surgery, chemotherapy and metastasis status.…”
Section: Discussionmentioning
confidence: 99%
“…Many reporters suggested other prognostic indicators such as lactate dehydrogenase (LDH), albumin count and relative platelet and blood indication levels, such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and lymphocyte to monocyte ratio (LMR) [10][11][12][13]. Given the fact of different risk factors were found about the prognosis of BC, lots of prognostic models have been established [14][15][16].…”
Section: Introductionmentioning
confidence: 99%